EXPLORING THE IMPACT OF DISCUSSION METHOD ON NIGERIA'S JUNIOR SECONDARY SCHOOL STUDENTS' READING COMPREHENSION: THE ROLE OF SOCIAL CONSTRUCTIVISM - Umar , Rashida; Ibrahim, Aisha Abdullahi (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
The discussion method is an instructional teaching method that utilises guided interaction to highlight a particular subject matter to facilitate the student. It is generally assessed as a successful teaching method that enhances learning through collaboration and gives students room to develop their communication, men, and critical thinking skills. Through applying Social Constructivism, a classical learning theory developed by Vygotsky (1968), we explored the impact of the discussion method on Nigeria's junior secondary school students' reading comprehension. Our findings reveal that an understanding of reading comprehension should be based on the social constructivist nature of reading. Teachers must be responsible enough to carry out their duties in the class, and motivation is central in inculcating knowledge in students. We recommend that Nigerian teachers consider students' learning environment, cultures, and social experiences and tailor their lessons to accommodate these factors.